2016
DOI: 10.1126/science.aac6633
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic (re)programming of caste-specific behavior in the ant Camponotus floridanus

Abstract: Eusocial insects organize themselves into behavioral castes whose regulation has been proposed to involve epigenetic processes, including histone modification. In the carpenter ant Camponotus floridanus, morphologically distinct worker castes called minors and majors exhibit pronounced differences in foraging and scouting behaviors. We found that these behaviors are regulated by histone acetylation likely catalyzed by the conserved acetyltransferase CBP. Transcriptome and chromatin analysis in brains of scouti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
212
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(225 citation statements)
references
References 53 publications
8
212
2
3
Order By: Relevance
“…Social insects may also provide unique insights into the regulation of longevity; the social castes of ants and bees have distinct behaviors, reproductive capacity, and life-spans that could serve as a model for the role of chromatin in aging. Comparisons between individuals from different castes have revealed that they have caste-specific DNA methylation and H3K27ac patterns that are functionally important for their behavior (Simola et al, 2016; Yan et al, 2015). It is unknown if caste-specific chromatin states affect lifespan, but this will be an exciting question to address in the future.…”
Section: Epigenomic Regulation Is Connected To Other Aging Hallmarksmentioning
confidence: 99%
“…Social insects may also provide unique insights into the regulation of longevity; the social castes of ants and bees have distinct behaviors, reproductive capacity, and life-spans that could serve as a model for the role of chromatin in aging. Comparisons between individuals from different castes have revealed that they have caste-specific DNA methylation and H3K27ac patterns that are functionally important for their behavior (Simola et al, 2016; Yan et al, 2015). It is unknown if caste-specific chromatin states affect lifespan, but this will be an exciting question to address in the future.…”
Section: Epigenomic Regulation Is Connected To Other Aging Hallmarksmentioning
confidence: 99%
“…Honey bee workers transition through cell cleaning, nursing, food processing and comb building, and foraging, distinct behavioral roles performed by discrete “temporal castes” (Seeley 1982; Johnson 2007), resulting in marked spatial separation of work (Baracchi and Chi 2014). Age-based division of labor is in part regulated by variation in response thresholds (Beshers and Fewell 2001; Rueppell et al 2006; Tsuruda et al 2008; Tsuruda and Page 2009), which are influenced by hormones (Marco Antonio et al 2008; Dolezal et al 2012), experience (Ravary et al 2007), social interactions (Ito and Higashi 1991; Powell and Tschinkel 1999; Greene and Gordon 2007; Gordon 2010; Pinter-Wollman et al 2013), genotype (Tsuruda and Page 2009; Constant et al 2012), and epigenetic factors (Simola et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the ant Camponotus floridanus, a differential recruitment of CBP to enhancer sequences in different castes (female minors, female majors, and males) has been reported (Simola et al 2013b). Furthermore, histone acetylation has been shown to be involved in regulating task-specific behavior in these ants (Simola et al 2016). These results suggest a prominent role for CBP-and, accordingly, CREB-dependent gene activation in processes related to task-specific behavior of these castes.…”
Section: A Role Of Pamcreb-associated Stimulus Responsiveness In Foramentioning
confidence: 88%